Land Changes Fostering Atlantic Forest Transition in Brazil: Evidence from the Paraíba Valley. Issue 1 (2nd January 2017) - Bicudo da Silva, Ramon Felipe; Batistella, Mateus; Moran, Emilio Federico; Lu, Dengsheng
Abstract : The Atlantic Forest biome has only 13 percent of its pristine vegetation cover left. This article analyzes the consequences of land changes on forest cover in the Paraíba Valley, São Paulo state, Brazil, from 1985 to 2011. Multitemporal satellite image classifications were carried out to map eight land use and land cover classes. The forest cover increased from 2, 696 km 2 in 1985 to 4, 704 km 2  in 2011, mostly over areas of degraded pastures. The highest rates of afforestation were observed within protected areas around eucalyptus plantations. On the other hand, deforestation processes were concentrated on areas covered by secondary forests. Socioeconomic changes taking place in particular Brazilian settings, such as industrialization and agricultural modernization, allied to the Paraíba Valley's natural biophysical constraints for agricultural production, have led the region to experience a remarkable case of forest transition.